The effects of consumer ethnocentrism, country of origin and animosity on Bangladeshi consumers' willingness to buy foreign products - Karim, Khondaker Sazzadul (Kulliyah of Economics and Management Science, International Islamic University Malaysia, 2016)
Over the last few decades, globalization and the openness of markets worldwide have extended the potential consumer from absolutely domestic base to international consumers. It is critical for international marketers to precisely evaluate consumers' willingness to buy the foreign made products. Therefore, to evaluate the acceptance in foreign market and to build up the competitive advantage that will be sustainable in the long run these issues need to be studied. Regardless of the significance of analyzing consumer product perceptions, there is a research gap in modelling the relationship of essential determinants that affect the consumers' willingness to buy foreign products. The general objective of this study is to understand the interrelationship among consumer ethnocentrism, country of origin, and animosity on Bangladeshi consumers' willingness to buy foreign products.The theory of planned behaviour and other supporting theories were applied as the theoretical foundation for developing the conceptual model. The conceptual framework of this study proposed that consumer ethnocentrism, country of origin, and animosity have a huge impact on willingness to buy of foreign products. The research also aims at examining the mediating role by product judgement among consumers ethnocentrism, country of origin, and animosity with consumers' willingness to buy. Utilizing the drop-off/get back method, which utilized a self-administered questionnaire, an empirical data survey was conducted in seven divisional territories of Bangladesh, i.e., Dhaka, Chittagong, Khulna, Rajshahi, Sylhet, Barisal and Rangpur. Questionnaires were distributed to 525 respondents through random sampling method. Analysis of data was then conducted using descriptive, exploratory and confirmatory factor analysis. Subsequently, structural equation modelling (SEM) with 467 respondents was conducted to test the 7 hypotheses of this study, including the mediating effect of product judgement on the relationship between consumer ethnocentrism, country of origin, and animosity with willingness to buy foreign made products. The results indicate that except country of origin the other two variables, e.g. consumer ethnocentrism and animosity were found significant with willingness to buy foreign products in Bangladesh. Furthermore, the results also reveal that product judgement can significantly mediate the relationship between consumer ethnocentrism, country of origin and animosity with willingness to buy foreign products. Developing a structural model, the study clarified willingness to buy foreign products and tested for goodness-of-fit. Upon its validation, the direct and mediated effects proposed by the study were also examined within the model. This study made theoretical and practical contributions, particularly on the part of product judgement as a mediator role among variables: customer ethnocentrism, country of origin and animosity with willingness to buy. Besides, this thesis also recognizes some vital indications for international marketers and retailers of foreign made items as to the negative dispositions of Bangladeshi consumers emerging from ethnocentric propensities and animosity feelings. Possibly, the demographic profile of these customers will assist marketers in segmenting the global market. Targeting on the right segments to offer their products and in addition to formulating appropriate marketing strategies will go a long way to producing the desired outcome in international marketing.